2015
DOI: 10.14254/2071-789x.2015/8-3/19
|View full text |Cite
|
Sign up to set email alerts
|

Family Decisions on the Tourist Market

Abstract: ABSTRACT. The purpose of this article is to present the specificity of family decisions on the tourist market. The first part of the article describes the four models of family decision-making and identifies the determinants of making joint and individual decisions. The second part discusses the profiling of a tourist whose tourist-trip-related family decisions are made jointly and of a tourist whose decisions in this respect are dominated by the family member whose income is the highest. Moreover, the areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
14
0
6
Order By: Relevance
“…Furthermore, children and their families can enjoy themselves and their opinion of what constitutes a healthy lifestyle can be reinforced. Furthermore, it is predicted that tourism for families with children will grow more than any other form of tourism, since a family vacation offers an opportunity for family members to be united and spend time together (Niemczyk 2015). Another larger share of visitors (28%) is represented by couples who spend a period of their vacations in agritourism structures, often as part of their honeymoon.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, children and their families can enjoy themselves and their opinion of what constitutes a healthy lifestyle can be reinforced. Furthermore, it is predicted that tourism for families with children will grow more than any other form of tourism, since a family vacation offers an opportunity for family members to be united and spend time together (Niemczyk 2015). Another larger share of visitors (28%) is represented by couples who spend a period of their vacations in agritourism structures, often as part of their honeymoon.…”
Section: Resultsmentioning
confidence: 99%
“…On family vacation decisions there has been argued that adolescent participation is minor or null in the final stage (Khoo-Lattimore et al 2016, Watne and Winchester 2011, Kaur and Medury 2011, Carr 2006. Niemczyk (2015) in his study on holidays decisions, concluded that adolescents have some say in the final decision solely in the case of domestic holidays, but they do not participate in that phase when it is concerned holidays more planned and abroad. Ashraf and Khan (2016) found an adolescent "decline in the involvement may be because family vacation is a high-budget decision and parents might be more involved in the final decision-making stage" (Ashraf and Khan 2016: 396).…”
Section: The Adolescent Rolementioning
confidence: 99%
“…The substantial and growing adolescent market needs marketers to understand the adolescent purchase behavior for current sales and their participation in the family structure (Niemczyk 2015, Srivastava 2015, Shahrokh and Khosravi 2014, Yang et al 2014. There is a good stream of research which has shown that adolescents' role in family purchase decisions varying by product, decision stage, adolescent, parental, and family characteristics (Aleti et al 2015, Ishaque and Tufail 2014, Shahrokh and Khosravi 2014, Shergill et al 2013, Ali et al 2013, Chaudhary and Gupta 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that competition between countries, cities and tourism enterprises is still growing and is becoming only stronger (Herget, Petrů & Abrhám, 2015), it is important to focus primarily on consumer needs. On the tourist market, the importance of well-chosen marketing tools is even higher if the target client is family with children, as participation of children in tourism decision-making process may be crucial because parents are satisfied only if their child is happy (Niemczyk, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%